CYP1B1-derived epoxides modulate the TRPA1 channel in chronic pain - Lili Sun; Jie Zhang; Changshan Niu; Cassandra E. Deering-Rice; Ronald W. Hughen; John G. Lamb; Katherine Rose; Kevin M. Chase; Marysol Almestica-Roberts; Markel Walter; Eric W. Schmidt; Alan R. Light; et al. (Elsevier, 2023)
Pain is often debilitating, and current treatments are neither universally efficacious nor without risks. Transient receptor potential (TRP) ion channels offer alternative targets for pain relief, but little is known about the regulation or identities of endogenous TRP ligands that affect inflammation and pain. Here, transcriptomic and targeted lipidomic analysis of damaged tissue from the mouse spinal nerve ligation (SNL)-induced chronic pain model revealed a time-dependent increase in Cyp1b1 mRNA and a concurrent accumulation of 8,9-epoxyeicosatrienoic acid (EET) and 19,20-EpDPA post injury. Production of 8,9-EET and 19,20-EpDPA by human/mouse CYP1B1 was confirmed in vitro, and 8,9-EET and 19,20-EpDPA selectively and dose-dependently sensitized and activated TRPA1 in overexpressing HEK-293 cells and Trpa1-expressing/AITC-responsive cultured mouse peptidergic dorsal root ganglia (DRG) neurons. TRPA1 activation by 8,9-EET and 19,20-EpDPA was attenuated by the antagonist A967079, and mouse TRPA1 was more responsive to 8,9-EET and 19,20-EpDPA than human TRPA1. This latter effect mapped to residues Y933, G939, and S921 of TRPA1. Intra-plantar injection of 19,20-EpDPA induced acute mechanical, but not thermal hypersensitivity in mice, which was also blocked by A967079. Similarly, Cyp1b1-knockout mice displayed a reduced chronic pain phenotype following SNL injury. These data suggest that manipulation of the CYP1B1-oxylipin-TRPA1 axis might have therapeutic benefit.